2015
DOI: 10.1007/s10620-015-3523-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Mitochondrial DNA Content Associated with the Risk of Liver Cirrhosis: A Nested Case–Control Study

Abstract: Low circulating mtDNA content may confer an increased cirrhosis risk in HBV patients. Further prospective studies are warranted to validate these findings and explore the clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The alteration of mtDNA content can profoundly impair oxidative phosphorylation, calcium‐dependent stress signaling, adaptive metabolic responses, and innate immune system . A decrease level of mtDNA content has been documented in cirrhosis and HCC . The chronic HBV infection is an early stage of cirrhosis and HCC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The alteration of mtDNA content can profoundly impair oxidative phosphorylation, calcium‐dependent stress signaling, adaptive metabolic responses, and innate immune system . A decrease level of mtDNA content has been documented in cirrhosis and HCC . The chronic HBV infection is an early stage of cirrhosis and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…13 A decrease level of mtDNA content has been documented in cirrhosis and HCC. 9,10 The chronic HBV infection is an early stage of cirrhosis and HCC. However, unlike in cirrhosis and HCC patients, it's reported that HBV patients receiving nucleos(t)ide analogs (NAs) have higher levels of mtDNA content compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations